The Association of Single-Nucleotide Polymorphisms in the MMP-9 Gene with Normal Tension Glaucoma and Primary Open-Angle Glaucoma. (3rd April 2018) - Suh, Wool; Won, Hong-Hee; Kee, Changwon
ABSTRACT: Purpose : To evaluate the association of matrix metalloproteinases (MMP)-9 gene polymorphisms with normal tension glaucoma (NTG) and primary open-angle glaucoma (POAG) in the South Korean population. Materials and Methods : A total of 700 South Korean subjects were recruited: 146 patients with NTG, 174 patients with POAG, and 380 healthy adults. Five single-nucleotide polymorphisms (SNPs; rs3918429, rs2274755, rs3787268, rs3918261, and rs3918270) of MMP-9 were analyzed in all subjects. The association with each disease was tested using an allelic χ 2 test and p values were corrected by permutation tests with 100 000 permutations. Results : Among the five SNPs, rs2274755 showed a significant association with NTG ( p = 0.021). The T allele of rs2274755 had an allelic odds ratio of 1.67 (95% confidence interval, 1.12–2.50). The association remained significant after correction using permutation tests ( p = 0.039). It was also significant in an association analysis for genotype frequency ( p = 0.011). The SNP was predicted to be found within a splicing site and a conserved region. No SNPs analyzed were significantly associated with POAG ( p > 0.05). Conclusions : The rs2274755 SNP in the MMP-9 gene was significantly associated with NTG. This supports a possible role of the MMP-9 gene in NTG pathogenesis.